Integrasi Teknologi dalam Pendidikan Matematika: Wawasan dari Tinjauan Literatur Sistematik: TECHNOLOGY INTEGRATION IN MATHEMATICS EDUCATION: INSIGHTS FROM A SYSTEMATIC LITERATURE REVIEW - Muhammad Fathurrahman; Putri Dini Retno Pratiwi; Marice Awairaro; Nazmi Al-lahmadi; Salima Silayar; Ismail Djakaria (Universitas Muhammadiyah Sorong, 2024)
This research aims to conduct a systematic literature review to uncover research trends related to Technology and Mathematics. The research method applied in this study is the Preferred Reporting Items for Systematic Reviews, using 3,812 scholarly articles from the Dimensions database. Article reviews were performed using the VOSviewer application. The results of the studyof reveal that main trends in the